The Political Economy of News Reporting and Poverty in Nigeria - Joshua Suleiman; Olusegun Ojomo (European Scientific Journal, ESJ, 2019)
This paper examines the political and economic factors that underpin Nigeria’s media. It seeks to understand whether these factors influence media content and invariably, poverty level in the country. Nigeria’s economy has depreciated over the past few decades. Unemployment stands at 23 per cent, with more than half a million of the citizens living on less than $1.90 a day, more than any other country on earth (Knoema, 2011; The Economist, 2019). The paper arguesthat if the Nigerian media could positively impact the growth of democracy and strengthen democratic institutions as they did in the past, they could also facilitate economic development, and poverty reduction in the country through news reporting. After all, one of the major features of democracy is to seek the happiness of the majority of the citizens by adequately providing for their wellbeing. It is therefore important to assess how the Nigerian media can provide useful information that can ensure poverty reduction. This paper draws on review of past studies, journal articles, newspaper and online publications in the related area. The paper recommends that the National Broadcasting Commission should mandate broadcast organizations to devote 80 percent of their broadcast to development information, events and conditions about the people of the state where they operate.